2021
DOI: 10.3390/cancers13215424
|View full text |Cite
|
Sign up to set email alerts
|

Peanut-Shaped Gold Nanoparticles with Shells of Ceragenin CSA-131 Display the Ability to Inhibit Ovarian Cancer Growth In Vitro and in a Tumor Xenograft Model

Abstract: Gold nanoparticles-assisted delivery of antineoplastics into cancerous cells is presented as an effective approach for overcoming the limitations of systemic chemotherapy. Although ceragenins show great potential as anti-cancer agents, in some tumors, effective inhibition of cancer cells proliferation requires application of ceragenins at doses within their hemolytic range. For the purpose of toxicity/efficiency ratio control, peanut-shaped gold nanoparticles (AuP NPs) were functionalized with a shell of cerag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 79 publications
1
1
0
Order By: Relevance
“…STEM image results demonstrated that H-AuNFs have a different morphology consisting of poly-dispersed, triangle, pentagon, and nearly spherical shapes, while R-AuNFs are nearly spherical. In the literature [ 72 , 73 , 74 , 75 ] spherical, triangular, and hexagonal gold nanoparticles have been reported; however, in this study, flower-shaped nanoparticles were also obtained in agreement with Borah et al [ 24 ].…”
Section: Discussionsupporting
confidence: 91%
“…STEM image results demonstrated that H-AuNFs have a different morphology consisting of poly-dispersed, triangle, pentagon, and nearly spherical shapes, while R-AuNFs are nearly spherical. In the literature [ 72 , 73 , 74 , 75 ] spherical, triangular, and hexagonal gold nanoparticles have been reported; however, in this study, flower-shaped nanoparticles were also obtained in agreement with Borah et al [ 24 ].…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, we would like to note that histopathological analysis of bladder samples collected from treated animals confirmed that the markers of inflammation (tissue edema, exfoliation of transitional epithelial cells, invasion of inflammatory cells in the mucosa, fibrosis of the lamina propria, and bladder mucosa hyperplasia) were considerably decreased in ceragenin-treated animals when compared to control ones. Moreover, the ability of ceragenin to diminish inflammation induced by pathological process was also presented by our research team when analyzing the anti-cancer activities of CSA-131 and its nanosystem 61 . A compelling body of evidence confirms also that the elastic modulus is an important factor influencing bacterial attachment, growth and biofilm formation, suggesting that the stiffening of tissues upon ceragenin administration in UTI-suffering animals creates an environment unfavorable for bacteria replication and virulency.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, different methods are used to assess the biocompatibility of nanoparticles, ranging from quantitative assays using conversion of compounds such as 3-(4, 5dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide (MTT) [257], 2, 3-bis-(2-methoxy-4nitro-5-sulfophenyl)-2H-tetrazolium-5-carboxanilide (XTT) [258] or lactate dehydrogenase (LDH) [257], through qualitative studies (live and/or dead cell staining assays using dyes such as calcein-AM with propidium iodide [259] and dual acridine orange/ethidium bromide staining [260]) and finally blood hemolysis assays [261] and animal model [262] to assess biocompatibility.…”
Section: Biocompatibility Of Metallic Nanoparticlesmentioning
confidence: 99%